Exact order of relative widths of classes $W^r_1$ in the space $L_1$ - Parfinovych, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
As $n → ∞$ the exact order of relative widths of classes $W^r_1$ of periodic functions in the space $L_1$ is found under restrictions on higher derivatives of approximating functions.